2010
DOI: 10.1097/aln.0b013e3181f79a69
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anesthetic Technique on Serum Vascular Endothelial Growth Factor C and Transforming Growth Factor β in Women Undergoing Anesthesia and Surgery for Breast Cancer

Abstract: Background:In breast cancer, vascular endothelial growth factor C, transforming growth factor ␤, placental growth factor, and fibroblast growth factor (acidic and basic) promote angiogenesis and metastases. We tested the hypothesis that a propofol-paravertebral anesthetic (PPA) technique would attenuate postoperative changes in these angiogenic factors to a greater extent than balanced general anesthesia (GA) and morphine analgesia in women undergoing surgery for primary breast cancer. Method: Forty women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 35 publications
1
73
1
5
Order By: Relevance
“…RAA was confirmed to inhibit the surgical stress response, as indicated by lower plasma glucose, cortisol, and C-reactive protein in RAA patients compared to general anesthesia/morphine analgesia-but RAA did not seem to affect the postoperative percent change in pro-angiogenic factors VEGF and prostaglandin E2 [93]. In contrast, regional anesthesia/analgesia decreased circulating TGF-β and IL-1β and attenuated the postoperative increase in lymphangiogenic VEGF-C and in pro-invasion, pro-metastatic, and pro-angiogenic MMP-9 [94,95]. Lastly, in an ex vivo experiment, the serum from general anesthesia/morphine analgesia patients was shown to promote cancer cell proliferation without affecting cancer cell migration when compared to the serum of patients undergoing RAA [96].…”
Section: Perioperative Opioids In Tumor Surgery Patientscontrasting
confidence: 45%
“…RAA was confirmed to inhibit the surgical stress response, as indicated by lower plasma glucose, cortisol, and C-reactive protein in RAA patients compared to general anesthesia/morphine analgesia-but RAA did not seem to affect the postoperative percent change in pro-angiogenic factors VEGF and prostaglandin E2 [93]. In contrast, regional anesthesia/analgesia decreased circulating TGF-β and IL-1β and attenuated the postoperative increase in lymphangiogenic VEGF-C and in pro-invasion, pro-metastatic, and pro-angiogenic MMP-9 [94,95]. Lastly, in an ex vivo experiment, the serum from general anesthesia/morphine analgesia patients was shown to promote cancer cell proliferation without affecting cancer cell migration when compared to the serum of patients undergoing RAA [96].…”
Section: Perioperative Opioids In Tumor Surgery Patientscontrasting
confidence: 45%
“…The results showed a mean post-operative change in VEGF concentrations among GA patients of 733 versus 27 pg/ml for paravertebral and TIVA patients [difference, 706 (97.5 % CI 280-1130) pg/ml, P = 0.001]. In contrast, the mean post-operative change in transforming growth factor b concentration among GA patients was -163 versus 146 pg/ml for paravertebral and TIVA patients [difference 309 (97.5 % CI -474 to -143) pg/ml, P = 0.005] [17]. Both VEGF and transforming growth factor b are important for the proliferation of tumor cells and angiogenesis.…”
Section: Regional Anesthesiamentioning
confidence: 69%
“…In another series of clinical studies, the authors randomized patients with breast cancer undergoing mastectomy to general anesthesia with sevoflurane-opioid versus propofol-paravertebral block. They found that the serum of those patients who received propofol-paravertebral block inhibited in vitro breast cancer cell proliferation but not migration and had better control of stress response markers, metalloproteinases, and transforming growth factor b but higher levels of vascular endothelial growth factor C [9,10,26,31].…”
Section: Regional Analgesia and Breast Cancer Recurrencementioning
confidence: 99%